2011
DOI: 10.1038/nature10366
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a relativistic outflow in the unusual γ-ray transient Swift J164449.3+573451

Abstract: Active galactic nuclei, which are powered by long-term accretion onto central supermassive black holes, produce relativistic jets with lifetimes of at least one million years, and the observation of the birth of such a jet is therefore unlikely. Transient accretion onto a supermassive black hole, for example through the tidal disruption of a stray star, thus offers a rare opportunity to study the birth of a relativistic jet. On 25 March 2011, an unusual transient source (Swift J164449.3+573451) was found, pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
493
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 414 publications
(524 citation statements)
references
References 19 publications
29
493
1
1
Order By: Relevance
“…We conclude with several important implications of our results. First, the velocity and kinetic energy of the outflow in ASASSN14li are significantly lower than inferred for the two relativistic γ-ray TDEs previously detected in the radio (Figure 6), which represent  a few percent of the TDE population (Bloom et al 2011;Burrows et al 2011;Zauderer et al 2011;Mimica et al 2015). Although the TDE sample with detected radio emission is small, this is reminiscent of the same relation observed in Type Ib/c core-collapse supernovae (Type Ib/c SNe) and long-duration gamma-ray bursts (LGRBs), in which a small fraction of events (LGRBs: ∼1% by volumetric rate) produce energetic relativistic outflows while the bulk of the population (Type Ib/c SNe) produces lower energy non-relativistic outflows ( Figure 6; Margutti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conclude with several important implications of our results. First, the velocity and kinetic energy of the outflow in ASASSN14li are significantly lower than inferred for the two relativistic γ-ray TDEs previously detected in the radio (Figure 6), which represent  a few percent of the TDE population (Bloom et al 2011;Burrows et al 2011;Zauderer et al 2011;Mimica et al 2015). Although the TDE sample with detected radio emission is small, this is reminiscent of the same relation observed in Type Ib/c core-collapse supernovae (Type Ib/c SNe) and long-duration gamma-ray bursts (LGRBs), in which a small fraction of events (LGRBs: ∼1% by volumetric rate) produce energetic relativistic outflows while the bulk of the population (Type Ib/c SNe) produces lower energy non-relativistic outflows ( Figure 6; Margutti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is the same model used to fit the radio emission from the relativistic TDE Sw J1644+57 (Zauderer et al 2011(Zauderer et al , 2013Berger et al 2012), as well as from core-collapse SNe and GRBs. We follow the procedures of Barniol Duran et al (2013) by assuming the outflow energy is minimized when the electron and magnetic field energy densities are in equipartition (Pacholczyk 1970;Scott & Readhead 1977;Chevalier 1998).…”
Section: Synchrotron Emission Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The areal densities of type Ibc supernovae(SNe Ibc; Berger et al 2003;Soderberg et al 2006b), low-luminosity GRBs(LLGRB; Soderberg et al 2006a;Barniol Duran et al 2015), and tidal disruption events(TDEs) without strong jets Holoien et al 2015;van Velzen et al 2016) are so small that it will be quite rare to detect them as false positive transients. Although off-axis long GRBs(LGRBs; van Eerten et al 2010; Ghirlanda et al 2014) and tidal disruption events with strong jets (TDE(jet); Burrows et al 2011;Zauderer et al 2011;Berger et al 2012) can be false positive transients, they will be identified earlier through their optical counterparts or can be filtered by identifying their host galaxies since the typical distance of these events is far beyond the detectable distance of the GW networks.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 99%
“…Most TDE candidates more or less show the above properties. Swift J164449.3+573451 and Swift J2058.4+0516 are two exceptions, which are hard X-ray transients and are probably due to observation of a relativistic jet pointed toward us [15][16][17].…”
Section: Introductionmentioning
confidence: 99%